The interplay between sugarcane (saccharum officinarum l.) production and climate change in Fiji islands: Challenges and adaptation strategies - Khan, Shifadjzic (International Journal of Sustainable Agricultural Research, 2025)
Sugarcane (Saccharum officinarum L.) has been a fundamental component of Fiji's economy; however, climate change presents considerable challenges, such as increasing temperatures, unpredictable precipitation, and severe weather occurrences. This research examines the effects of global warming on sugarcane yields in Fiji, identifies the primary factors contributing to decreased productivity, and explores adaptive strategies for sustainable cultivation. A systematic review of relevant literature was conducted utilizing academic databases, concentrating on climate-induced challenges and mitigation strategies. This analysis examines the environmental, agronomic, and economic implications, highlighting emissions from fertilizers, machinery, and vehicles as factors contributing to land degradation, human health risks, and resource depletion. Possible solutions encompass the development of climate-resilient cultivars, the adoption of eco-friendly farming practices, and the implementation of robust policy frameworks. The findings indicate that climate change has significantly diminished sugarcane yields in Fiji, while emissions from agricultural practices have intensified ecosystem degradation. Adaptive measures, including enhanced agronomic practices and resilient crop varieties, demonstrate potential in addressing these challenges. Collaborative policymaking and active stakeholder engagement are critical for enhancing resilience and ensuring long-term sustainability. In summary, Fiji's sugarcane industry necessitates immediate interventions via sustainable agricultural practices, strategic planning, and policy integration to adapt to climate changes and maintain its economic importance.